Comparison of bond strength of two porcelains and two base metal alloys in metal-ceramic restorations - Asadollah Ahmadzadeh; Saghar Ghanavati (Wolters Kluwer Medknow Publications, 2019)
Background: The purpose of this study was to evaluate the bond strength between two porcelains (VITA VMK Master and VITA VM13) and two types of base metal alloys (Ceramill Sintron and Verabond). Materials and Methods: In an experimental study, 20 rectangular strips (25 mm × 4 mm × 0.5 mm) of each base metal alloy (Ceramill Sintron and Verabond) were fabricated according to the manufacturer's instructions. After sandblasting and polishing, the samples were placed in an ultrasonic device to remove surface contaminants. A surface of 8 mm × 4 mm × 1 mm of samples was veneered with Vita VM13 and VITA VMK Master. The samples were divided into four groups (n = 10 each group; VM13/Ceramill, VMK Master/Ceramill, VM13/Verabond, and VMK Master/Verabond), and bond strength was evaluated by three-point bending test with a universal testing machine. Two-way ANOVA was used for comparison in each group, post hoc Scheffe's test was used for analyzing data between groups, and the Kolmogorov-Smirnov test was used for the normality (P < 0.05). Results: The maximum bond strength was related to Verabond/VM13 (44.35 ± 7.9 MPa) and then the Ceramill Sintron/VM13 (39.33 ± 4.43 MPa), and the lowest was related to the Ceramill Sintron/VMK Master (29.75 ± 3.2 MPa). There was no significant difference between bond strength of VM13 with the two alloy groups (P > 0.05), and bond strength of VMK Master to Ceramill Sintron CAD/CAM alloy was less than the conventional Verabond alloy (P < 0.05); however, bond strength of all the groups was above the standard threshold (25 MPa). Conclusion: Based on the results of this study, the bond strength of the porcelain to Verabond was better, but the bond strength of the porcelain to Ceramill Sintron also was not less than the standard threshold; thus, this new CAD/CAM alloy can be an alternative to the conventional base metal alloys in the metal-ceramic restorations.